1992
DOI: 10.1192/bjp.161.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment with Noradrenalin and Serotonin Reuptake Inhibitors in Resistant Depression

Abstract: Eight cases of resistant recurrent depression were treated with a combination of nortriptyline and a new serotonin reuptake inhibitor, with or without concurrent lithium therapy. Significant improvement was seen in all patients where other drug regimes and ECT had been ineffective. No adverse reactions occurred in any of our patients, seven of whom were elderly. The combination treatment was more effective than individual therapies alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 14 publications
0
52
0
3
Order By: Relevance
“…This procedure showed that noradrenaline (NA)-reuptake inhibitors (NRIs) and selective serotonin (5-hydroxytryptamine/ 5-HT)-reuptake inhibitors (SSRIs) increased selectively and respectively climbing and swimming behavior (Detke et al 1995b). This technique can thus distinguish components to the behavioral response to antidepressants (Lucki 1997), which is in agreement with distinguishable neurochemical and behavioral contributions to the therapeutic effects of antidepressants in humans (Heninger et al 1996;Katz et al 1994).Serotonin and noradrenaline systems are directly involved in the pathogenesis and the recovery from depression (Blier et al 1990;Caldecott Hazard et al 1991), and there were clinical suggestions that simultaneous enhancement of neurotransmission in both 5-HT and NA systems could provide increased efficacy and rapidity of antidepressants effects (Nelson et al 1991;Poirier and Boyer 1999;Seth et al 1992;Weilburg et al 1989). In the FST, however, the NRI desipramine dosedependently antagonized the swimming behavior produced by the SSRI fluoxetine (Rénéric and Lucki 1998).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This procedure showed that noradrenaline (NA)-reuptake inhibitors (NRIs) and selective serotonin (5-hydroxytryptamine/ 5-HT)-reuptake inhibitors (SSRIs) increased selectively and respectively climbing and swimming behavior (Detke et al 1995b). This technique can thus distinguish components to the behavioral response to antidepressants (Lucki 1997), which is in agreement with distinguishable neurochemical and behavioral contributions to the therapeutic effects of antidepressants in humans (Heninger et al 1996;Katz et al 1994).Serotonin and noradrenaline systems are directly involved in the pathogenesis and the recovery from depression (Blier et al 1990;Caldecott Hazard et al 1991), and there were clinical suggestions that simultaneous enhancement of neurotransmission in both 5-HT and NA systems could provide increased efficacy and rapidity of antidepressants effects (Nelson et al 1991;Poirier and Boyer 1999;Seth et al 1992;Weilburg et al 1989). In the FST, however, the NRI desipramine dosedependently antagonized the swimming behavior produced by the SSRI fluoxetine (Rénéric and Lucki 1998).…”
mentioning
confidence: 64%
“…Serotonin and noradrenaline systems are directly involved in the pathogenesis and the recovery from depression (Blier et al 1990;Caldecott Hazard et al 1991), and there were clinical suggestions that simultaneous enhancement of neurotransmission in both 5-HT and NA systems could provide increased efficacy and rapidity of antidepressants effects (Nelson et al 1991;Poirier and Boyer 1999;Seth et al 1992;Weilburg et al 1989). In the FST, however, the NRI desipramine dosedependently antagonized the swimming behavior produced by the SSRI fluoxetine (Rénéric and Lucki 1998).…”
mentioning
confidence: 99%
“…Indeed, treatments combining NE and S-HT reuptake blockade have been reported to produce more robust antidepressant effects in groups of depressed patients (Seth et al 1992;Nelson et al 1991;Poirier and Boyer 1999). Development of molecules acting as dual inhibitors of 5-HT and NE reuptake might thus lead to more efficacious antidepressant treatments.…”
Section: Noradrenergic and Specifie Serotollinergic Antidepressant: Mmentioning
confidence: 99%
“…However, antidepressant therapies that activate 5-HT or NE pathways have a latency of two to three weeks in response and only about 70-80% of patients are responders (Roose et al 1986;Thase and Rush 1995). Clinical studies have indicated that combination therapy with drugs that inhibit 5-HT and NE uptake and thereby enhance activity of both neuronal systems may have improved therapeutic efficacy and possibly a faster onset of activity compared to drugs that inhibit only one monoamine uptake system (Weilburg et al 1989;Nelson et al 1991;Seth et al 1992). The tertiary amine containing tricyclic antidepressants such as imipramine and amitriptyline inhibit both NE and 5-HT uptake in vitro to variable degrees and therefore may be considered dual uptake inhibitors.…”
mentioning
confidence: 99%